The Elasticity of Demand From Family Budgets - Pigou, A. C. (Quarterly Journal of Economics, 1933)
Journal Article The Elasticity of Demand from Family Budgets Get access A. C. Pigou A. C. Pigou King's College, Cambridge, England Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 47, Issue 2, February 1933, Page 342, https://doi.org/10.2307/1883692 Published: 01 February 1933